Four supernumerary teeth in central anterior maxilla: Report of a case. Issue 4 (July 2020) - Takahashi, Kosuke; Yamazaki, Fumie; Tajima, Mai; Suzuki, Mayu; Yano, Teruo; Kato, Yugo; Aoki, Akinobu; Ito, Ko; Kondoh, Toshirou
Abstract: Multiple supernumerary teeth in the central maxilla are an uncommon occurrence and teeth appear at an increased frequency in males, at nearly 2:1. The most frequent type of supernumerary tooth is located between the central inncisors in the anterior maxilla, with one or two supernumerary teeth; three supernumerary teeth are very rare. We report a case of four supernumerary teeth in the central maxilla occur in less than 1 % of cases in all supernumerary teeth. A 14-year-old girl was referred to our hospital for treatment of an unclear radiolucent lesion in the central maxillary region. Radiographic examination showed four supernumerary teeth. Clinical diagnosis was supernumerary teeth, and surgical extraction was performed with the patient under general anesthesia. The supernumerary teeth extracted were microdont and showed enamel formation, as well as a similar form as canines in the maxilla. At the 6-month follow-up evaluation, there was no evidence of recurrence.